Avaliação do efeito da estimulação magnética transcraniana nos sinais de eletroencefalograma usando o Teste F Espectral e a função de coerência - Massote, Mariana Aguiar (2018)
This work accomplishes an exploratory study of electroencephalogram signals (EEG) after transcranial magnetic stimulation (TMS). TMS is used for diagnosis and as a therapy for some illnesses, but there is difficulty in processing the artifact caused by discharging of TMS. The magnetic stimulator used was adjusted to provide biphasic pulses that lasted 280 µs and magnetic field generated has 31 kT for the biggest intensity point, and a 257-channel EEG recording equipment, which has a delta-sigma converter with a 20000-Hz sampling rate and register of 1000 Hz, was used. The signals were collected from 12 healthy volunteers. Spectral F Test was initially used with 4 one-second windows after the TMS stimulus and 4 one-second windows before the TMS, to check the effect of stimulation. The Beta Test was proposed using 4 onesecond windows before TMS stimulus and one one-second window after TMS, with the goal of comparing a more distant period after the stimulus and hence decreasing the artifact effect. The Beta Test has an analytic critic value and shows normalized result, which makes the volunteers results comparison easier. The results are in accordance with those accomplished by other research groups, in which there is an increase of the frequency potency until 30 Hz. However, this work considered a 5%-significance level, while other groups do not show statistics for the analysis. F Test results were lower than Beta Test, since Beta Test has more influence of the window immediately after the stimulus than the F Test.